THE INFLUENCE OF INSTAGRAM SOCIAL MEDIA PROMOTION ON INTEREST IN VISITING POSBLOC CREATIVE PUBLIC SPACES, CENTRAL JAKARTA - Maudiarti, Santi; Taviprawati, Ervina; Alfati Alida, M. Rafli (Universitas Islam Lamongan, 2023)
PosBloc makes Instagram social media look very attractive so that many people are interested in visiting PosBloc. From Instagram, PosBloc has many benefits, one of which is introducing PosBloc to a large audience so that someone's interest in visiting PosBloc, Central Jakarta increases. The purpose of conducting this research is to gain new knowledge regarding the influence of Instagram social media on the desire to visit PosBloc, Central Jakarta. The method used in this research is a quantitative descriptive approach. Data collection techniques in this research include documentation, literature study, and questionnaires. Primary data processing was assisted by the SPSS 25 program. Respondents from this study were 100 who had visited PosBloc aged <18 to >29 years. The results of the T test researchers concluded that the T value was 29.259 with a significance of 0.00<0.05. So this equation can be used to predict the social media variable Instagram (X). It can be concluded that the influence of the social media variable Instagram (X) on visiting interest (Y) is partially accepted.